2002
DOI: 10.1074/jbc.m109320200
|View full text |Cite
|
Sign up to set email alerts
|

SKF-82958 Is a Subtype-selective Estrogen Receptor-α (ERα) Agonist That Induces Functional Interactions between ERα and AP-1

Abstract: The transcriptional activity of estrogen receptors (ERs) can be regulated by ligands as well as agents such as dopamine, which stimulate intracellular signaling pathways able to communicate with these receptors. We examined the ability of SKF-82958 (SKF), a previously characterized full dopamine D1 receptor agonist, to stimulate the transcriptional activity of ER␣ and ER␤. Treatment of HeLa cells with SKF-82958 stimulated robust ER␣-dependent transcription from an estrogen-response element-E1b-CAT reporter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 85 publications
3
14
0
Order By: Relevance
“…Although the sequence (TGACACA) present in our ERE-E1b-CAT reporter diverges from the consensus TRE sequence, it has been shown to bind to in vitro translated Jun and Fos (56), and our gel mobility shift assays reveal that the levels of both c-Jun and c-Fos expressed in HeLa cells are sufficient to bind to this DNA. Moreover, our laboratory demonstrated previously through overexpression studies that c-Jun can enhance ER␣-mediated transcription of ERE-E1b-CAT but not of the corresponding TRE mutant reporter, ERE-E1b-CAT(mTRE) (39). Because we demonstrate a requirement for the ERE and TRE DNA sites, our data suggest that cooperation between ER and AP-1 transcription factors bound to their respective target promoter sequences results in robust forskolin/IBMX activation of target gene expression.…”
Section: Figmentioning
confidence: 62%
See 2 more Smart Citations
“…Although the sequence (TGACACA) present in our ERE-E1b-CAT reporter diverges from the consensus TRE sequence, it has been shown to bind to in vitro translated Jun and Fos (56), and our gel mobility shift assays reveal that the levels of both c-Jun and c-Fos expressed in HeLa cells are sufficient to bind to this DNA. Moreover, our laboratory demonstrated previously through overexpression studies that c-Jun can enhance ER␣-mediated transcription of ERE-E1b-CAT but not of the corresponding TRE mutant reporter, ERE-E1b-CAT(mTRE) (39). Because we demonstrate a requirement for the ERE and TRE DNA sites, our data suggest that cooperation between ER and AP-1 transcription factors bound to their respective target promoter sequences results in robust forskolin/IBMX activation of target gene expression.…”
Section: Figmentioning
confidence: 62%
“…In ERE-E1b-CAT such a putative TRE is located ϳ255 bp upstream from the ERE. To determine whether this TRE played any role in the ability of forskolin/ IBMX to stimulate the activity of either ER, we examined the ability of forskolin/IBMX to increase CAT gene expression from a reporter plasmid (ERE-E1b-CAT(mTRE)) in which the TRE was mutated to GGACTCA, a mutation previously demonstrated to abolish AP-1 binding (39,57). As shown in Fig.…”
Section: The Upstream Tre Enhancer In the Ere-e1b-cat Reporter Is Reqmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the inhibitory effects of estradiol on TGF-␤-sensitive and bone morphogenetic proteinsensitive Smads that occur in mesangial and breast cancer cells (69,70), estradiol enhances Smad-dependent gene expression in response to TGF-␤ in osteoblasts. Interactions between ERs and AP-1 transcription factors are also complex, because estrogen can either increase or decrease the expression of AP-1-sensitive genes (56,57,71,76). We found that estrogen reduced TGF-␤ activation of the AP-1-sensitive promoter 3TP-Lux.…”
Section: Fig 9 Runx2 Integrates Er-dependent Gene Expressionmentioning
confidence: 68%
“…The ability of MBG to bind to MR was determined in vivo essentially as previously described [20]. Briefly, 1 μg of the MR expression plasmid was transfected into Cos-1 cells using Lipofectamine and 24 h thereafter media was aspirated from wells and replaced with DMEM containing 5% sFBS and ∼1.0 nM …”
Section: Aldosterone Binding Assaymentioning
confidence: 99%